The Value of Software - Gómez-Cram, Roberto; Lawrence, Alastair (American Economic Review, 2025)
Software is one of the most important assets that needs to be priced in the digital economy. It has emerged as a disruptive technology, with companies primarily valued for their software offerings growing from 2 percent to 13 percent of market share between 1996 and 2023. We document persistent anomalies in growth forecasts and stock returns for software companies, indicating significant deviations from rational expectations over multiple decades. Our findings are consistent with Bayesian investors gradually learning about software’s growing importance, highlighting how markets can be very slow to discern fundamental shifts from transient shocks in noisy data. (JEL D22, G12, G32, L14, L86)